1986
DOI: 10.1055/s-2007-1001845
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathologische Veränderungen bei chronisch schizophrenen Patienten nach Neuroleptikaentzug: Beziehungen zu therapeutischen, neuroendokrinen und computertomographischen Variablen

Abstract: The following data were obtained from 36 male chronic schizophrenics (ICD 295.6) of 47 +/- 11 years of age, treated with neuroleptics for the last 16 +/- 6 years: Age, age at first manifestation of disease, duration and dosage scheme of neuroleptic therapy and number of electroconvulsive shock treatments. Blood samples were drawn both under neuroleptic treatment and after a 12-day withdrawal of neuroleptics, for determining cortisol, prolactin, beta-endorphin and noradrenaline. Psychopathology was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The serum pro lactin values, which had been elevated under neurolep tics, were rapidly restored to baseline values within 48-72 h (according to our data within 3-7 days). As expected, prolactin levels also decrease after withdrawal of long term neuroleptic medication in chronic schizophrenia [4,5,25]. Green et al [26] showed that the course of prolac tin values differed substantially in patients with previous ly high and low prolactin levels after withdrawal: only if baseline values were low did prolactin levels rise in the neuroleptic-free interval after an initially rapid fall from the 2nd weeks onwards [V-shaped course, cf.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The serum pro lactin values, which had been elevated under neurolep tics, were rapidly restored to baseline values within 48-72 h (according to our data within 3-7 days). As expected, prolactin levels also decrease after withdrawal of long term neuroleptic medication in chronic schizophrenia [4,5,25]. Green et al [26] showed that the course of prolac tin values differed substantially in patients with previous ly high and low prolactin levels after withdrawal: only if baseline values were low did prolactin levels rise in the neuroleptic-free interval after an initially rapid fall from the 2nd weeks onwards [V-shaped course, cf.…”
mentioning
confidence: 73%
“…Thus, the prolactin-stimu lating effect of haloperidol and its fall after discontinua tion of medication have no clearcut connection with the clinical benefit of suspension therapy. Data on the predic tive value of serum prolactin for the clinical effect of sub sequent neuroleptic withdrawal in chronic schizophrenic patients are divergent: Some authors [5,25,[29][30][31] found no statistically significant correlation between prolactin levels and psychopathological changes after neuroleptic withdrawal. In contrast, others [4,6,32,33] reported that patients with an unfavorable withdrawal effect (rapid relapse) have lower baseline prolactin levels than patients with a more favorable withdrawal effect.…”
mentioning
confidence: 99%